Innovating Authentic Reading Assessments: A Design Framework for Junior High School English Learners in Digital Contexts - Muamaroh; Idris, Bayu Romli Idris; Mauly Halwat Hikmat (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2026)
The shift towards digital literacy in contemporary education necessitates a reevaluation of traditional assessment methods, particularly in the context of junior high school English learners. Authentic reading assessments offer a promising solution by integrating real-world tasks and digital content. However, despite their benefits, there remains a notable gap in designing authentic assessments that are both engaging and effective for this demographic, especially in digital contexts. This study aims to address this gap by proposing a design framework for innovative, authentic reading assessments tailored for junior high school students in the digital age. The research objective is to develop a performance-based assessment that integrates digital texts, such as social media posts, to evaluate students' comprehension, critical thinking, and digital literacy skills. The design research approach involves creating a scenario where students read authentic digital texts and produce educational content, such as infographics, that reflect their understanding and analysis. Data collection will include students’ work samples, teacher feedback, and post-assessment reflections. Data analysis will focus on evaluating the alignment of students’ outputs with the criteria set forth in the rubric, particularly in terms of comprehension, analysis, and creativity. Preliminary results suggest that this framework encourages deeper engagement with texts and fosters skills necessary for digital literacy. The study contributes to the development of authentic assessments that bridge classroom learning with real-world applications, preparing students for the demands of the digital world.